Potential Use of Volcanic Ash as Filler Material in Hot Mix Asphalt - Basha Fayissa; Achalu Kebede; Fekadu Fufa (Advances in Civil Engineering)
Road construction often focuses on the use of conventional materials. Due to the depletion of these conventional materials, this cannot be always true. To overcome such problems, several alternative construction materials have been proposed as sustainable solutions. Thus, this study has investigated the potential use of volcanic ash (VA) as an alternative filler material in hot mix asphalt. The investigation has used laboratory scale and purposive sampling method for sample collection. The plastic index and specific gravity of volcano ash are 0.92% and 2.44, respectively. The chemical composition analysis indicated that VA is a class-N pozzolana material. Maximum stability of 11.38 kN was obtained at full replacement of volcano ash. The tensile strength ratio of the mix at full replacement of CSD and volcanic ash is 82% and 98%, respectively. From the fatigue resistance analysis, the probable failure of pavement constructed with the mixture containing VA could be improved from 16600 to 14400. Due to its rough surface, VA has better bonding ability with bitumen compared to CSD. The mix prepared from VA has less deformation tendency than that prepared from CSD.